Lower Performance in the Six-Minute Walk Test in Obese Youth With Cardiometabolic Risk Clustering - Valerio, Giuliana; Licenziati, Maria Rosaria; Tortorelli, Paola; Calandriello, Lidia Federica; Alicante, Paola; Scalfi, Luca (Frontiers in Endocrinology, 2018)
Background: Physical fitness is an important index of health. Our aim was to assess whether cardiorespiratory and/or musculoskeletal components of physical fitness were associated with cardiometabolic risk clustering in obese youth, using adapted and validated field tests. Methods: We evaluated 252 children and adolescents (132 males, 52.4%, mean age 10.9±1.9 years) with primary obesity. All subjects performed the 6-minute walk test (6MWT) for assessing aerobic fitness, the standing broad jump and the 30 s-chair stand tests for lower-body muscular strength, and the handgrip test for upper body isometric strength. Cardiometabolic risk (CMR) clustering was defined as having two or more of the following risk factors: high SBP and/or DBP, impaired fasting glucose, high triglycerides, and low HDL-Cholesterol. Results: CMR clustering was found in 44 (17.5%) obese youth. Youth with CMR clustering had a lower cardiorespiratory fitness, as assessed by 6MWT, compared to those without CMR clustering. On the contrary, no difference was found with respect to musculoskeletal fitness. The number of CMR factors were significantly associated with gender and BMI-SDS and negatively with age and 6MW distance. The 6MW distance was independently associated with age and negatively with sedentary time and CMR clustering. Conclusions: A lower performance in the 6MWT may be considered as an additional trait of CMR clustering in obese youth. The 6MWT may represent a valuable, simple and low cost test to estimate the cardiorespiratory fitness in youth with obesity.